Isolasi dan Karakterisasi Flavonoid dari Kulit Buah Manggis (Garcinia mangostana L.) - Sabariah Sabariah; Nazulis Z (Jurnal Periodic Jurusan Kimia UNP, 2013)
Have been done the isolation of flavonoids of the fruit hulls of mangosteen (Garcinia mangostana L.) in theChemistry Research Laboratory, Faculty of Mathematics and Sciences, State University of Padang. This research to isolate and know the characteristics of the compound flavonoid of the fruit hulls of mangosteen. Isolation method was used macerated with methanol, and followed by fractionation with n-hexane and ethyl acetate. Separation of ethyl acetate fraction by column chromatography using silica, ethyl acetate eluent used: methanol in SGP. Isolation purity test results performed by TLC and melting point. Pure flavonoids obtained as a yellow amorf 0.0012 g with a melting point range from 279.8 to 280.7˚C. Color reagent test results with10% NaOH, concentrated H2SO4, and Mg-HCl showed the presence of flavonoids. The test results showed stains KKt-2A is in the region aglycone: flavonols. From the data analysis,IR spectra showed the presence of the-OH, C-O-C ether and aromatic C=C. While the UV-Vis spectra showed the presence of a cluster of -OH on C-4’. From the above data allegedly isolated flavonoids is aflavonol with the-OH at C-4'.